The renaissance of confucianism in contemporary China - Fan, Ruiping; SpringerLink (Online Service). (Dordrecht, Netherlands Springer Netherlands, 2011)
The Renaissance of Confucianism in Contemporary China features an important school of Confucianism in Mainland China today, 'Political Confucianism' powerfully articulated by Jiang Qing, author of the leading article in this volume. 'Political Confucianism' is unique: on the political side, it rejects many core values of liberalism, the dominant political ideology in the West; and on the 'Confucianism' side, it rejects the one-sided emphasis on the inner sageliness of ?New Confucianism? developed in Hong Kong and Taiwan in the last century. In this volume, the programmatic essay by Jiang Qing is followed by penetrating essays, either further expanding on or critically examining various themes of Jiang's original essay, by eminent scholars, many of whom are committed Confucians themselves. The volume concludes with an informative biography of Jiang Qing. It is a must-read for anyone who is interested in learning about the situation of Confucianism in contemporary China in particular and about Confucianism or contemporary China in general.
Introduction. The rise of authentic Confucianism, Ruiping Fan--Part I. The Renaissance of Confucianism--1. From mind Confucianism to political Confucianism, Jiang Qing.- 2. The Rise of political Confucianism in contemporary China, Ruichang Wang--3. On 'one-continuity' in Jiang Qing's Confucian thought, Dan Lin--4. Jiang Qing on equality, Ruiping Fan--5. The Confucian conception of transcendence and filial piety, Qingxin K. Wang--6. Toward a proper relation between men and women: Beyond masculinism and feminism, Tangjia Wang--7. The soft power in the Confucian 'kingly way', Anthony Yeung--Part II. Critiques and responses--8. Jiang Qing's 'political Confucianism' , Daniel Bell.- 9. Declaration towards a global ethic? Jiang Qings Response, Jonathan Chan--10. Jiang Qing on the inevitable and permanent conflict between the Christian faith and confucian culture, Ping-cheung Lo--11. The characteristics and prospect of Confucian academies: a commentary on Jiang Qing's ideas on Confucian academies, Xiuping Hong--12. Three political Confucianisms and half a century, Albert H.Y. Chen --13. Is political Confucianism a universalism? an analysis of Jiang Qing's philosophical tendency, Xianglong Zhang.-  Part III. A note on Jiang Qing--14. A Confucian coming of age, Erika Yu and Meng Fan.
Electronic reproduction.
Keywords: Confucianism -- China -- 20th century